2009
DOI: 10.1111/j.1749-6632.2009.04606.x
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Development from Human Induced Pluripotent Stem Cells

Abstract: A decade of research on human embryonic stem cells (ESC) has paved the way for the discovery of alternative approaches to generating pluripotent stem cells.Combinatorial overexpression of a limited number of proteins linked to pluripotency in ESC was recently found to reprogram differentiated somatic cells back to a pluripotent state, enabling the derivation of isogenic (patientspecific) pluripotent stem cell lines. Current research is focusing on improving reprogramming protocols (e.g. circumventing the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 34 publications
4
66
0
2
Order By: Relevance
“…Induced pluripotent stem cells (iPSCs) are pluripotent cells derived from terminally differentiated cells by dedifferentiation. The generation of iPSCs creates the possibility of generating tissue-specific cells, including HSCs [63][64][65][66][67][68] or MSCs [69][70][71][72][73][74][75][76], but further study is required before clinical application of iPSCs can commence. Taken together, immune reconstruction and modification of genetic predisposition of hematopoietic stem cells are important for radical cure of IBD.…”
Section: Intestinal Stem Cells and Other Stem Cells In Ibdmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) are pluripotent cells derived from terminally differentiated cells by dedifferentiation. The generation of iPSCs creates the possibility of generating tissue-specific cells, including HSCs [63][64][65][66][67][68] or MSCs [69][70][71][72][73][74][75][76], but further study is required before clinical application of iPSCs can commence. Taken together, immune reconstruction and modification of genetic predisposition of hematopoietic stem cells are important for radical cure of IBD.…”
Section: Intestinal Stem Cells and Other Stem Cells In Ibdmentioning
confidence: 99%
“…In other studies, overexpression of Cdx4 in murine embryonic stem cells facilitated embryoid body and hematopoietic progenitor development and was associated with increased ABD HOX expression (27). Embryoid bodies engineered to co-overexpress Cdx4 and HoxB4 provided complete long term hematopoiesis in lethally irradiated mice, although neither protein had this function alone (28). Additionally, increased Cdx4 expression was documented in bone marrow cells from human subjects with AML (26).…”
mentioning
confidence: 93%
“…1 This year, a brief report in Blood concluded that host IL-17 reduces tumor growth and metastasis. 2 The authors' conclusions relied entirely on one C57BL/6 mouse-derived adenocarcinoma cell line, MC38, in which they showed a 5-fold or greater enhancement in subcutaneous growth and metastases in IL-17-deficient mice compared with control wild-type mice. Their conclusions also contrasted sharply with 3 important previous papers that suggested that IL-17 promoted tumor growth.…”
mentioning
confidence: 99%